Enhanced tensile ductility of an additively manufactured near-α titanium alloy by microscale shear banding. (October 2022) - Liu, Zhiying; Li, Renkai; Chen, Daolun; Sun, Yu; He, Bei; Zou, Yu
Highlights: Activating microscale shear bands (MSBs) provides a new opportunity to enhance tensile ductility of additively manufactured titanium alloys. The MSBs can be activated in the additively manufactured Ti-6Al-2Zr-Mo-V alloy with dispersed microscale α colonies. Phase-scale mechanical properties of additively manufactured Ti-6Al-2Zr-Mo-V alloy are measured by high-speed nanoindentation mapping and correlated with global mechanical properties. The dislocation-based formation mechanism of the MSBs in the additively manufactured Ti-6Al-2Zr-Mo-V alloy is discussed. Abstract: Laser-based directed energy deposition (LDED) enables rapid near-net-shape fabrication of large-scale titanium components for aerospace applications. However, the poor tensile ductility of most as-deposited titanium alloys, particularly near-α alloys, hinders their wide usage for critical load-bearing structures. Here we report that a high density of microscale shear bands (MSBs) can be activated in an LDED-produced Ti-6Al-2Zr-1Mo-1V alloy with dispersed microscale α colonies to enhance its tensile ductility. Using high-speed nanoindentation and in situ scanning electron microscopy tensile tests, we correlate the local micromechanical properties and global mechanical behavior of such a LDED-produced titanium alloy: (i) The soft α colonies with a hardness of ∼3.3 GPa produce slip bands (SLBs) with basal and prismatic < a >-slips; (ii) The surrounding hard α colonies or individual laths with a hardness of ∼4.4 GPa are plastically deformed by activating MSBs, which are assisted by pyramidal < a >- and < c  +  a >-slips. Our results suggest that the nucleation of MSBs relies on the degree of local shear stress acting on the hard domains. The local shear stress is determined by the domain size, spatial orientation, and mechanical contrast with vicinal soft domains. The propagation of MSBs can be arrested by the boundaries between hard and soft domains, suppressing the evolution of MSBs into macroscale catastrophic shear bands and, therefore, enhancing tensile ductility. Our study demonstrates that activating the MSBs provides a new opportunity to effectively enhance the ductility of LDED-produced titanium alloys and expedite the adoption of this additive manufacturing technology for critical structural applications. Graphical abstract: Image, graphical abstract